2016
DOI: 10.2298/csis141229041l
|View full text |Cite
|
Sign up to set email alerts
|

A novel animal migration algorithm for global numerical optimization

Abstract: Animal migration optimization (AMO) searches optimization solutions by migration process and updating process. In this paper, a novel migration process has been proposed to improve the exploration and exploitation ability of the animal migration optimization. Twenty-three typical benchmark test functions are applied to verify the effects of these improvements. The results show that the improved algorithm has faster convergence speed and higher convergence precision than the original animal migration optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Notice that η i (s) =η i /s as η i (t) =η i amounts to a step signal for constant vectorη. Using the final value theorem to (7), we have Therefore, it can be concluded that lim t→∞ e(t) 2 = η 2 /γ. Furthermore, the steadystate residual error lim t→∞ e(t) 2 decreases to zero as γ tends to positive infinity.…”
Section: Theoretical Analysesmentioning
confidence: 95%
See 1 more Smart Citation
“…Notice that η i (s) =η i /s as η i (t) =η i amounts to a step signal for constant vectorη. Using the final value theorem to (7), we have Therefore, it can be concluded that lim t→∞ e(t) 2 = η 2 /γ. Furthermore, the steadystate residual error lim t→∞ e(t) 2 decreases to zero as γ tends to positive infinity.…”
Section: Theoretical Analysesmentioning
confidence: 95%
“…Viewed as an essential step of many solutions, the online optimization often arises in mathematics and control theory, and finds its applications in numerical analysis [1], traffic control [2] machine learning [3], robotics [4][5][6] and animal migration analysis [7]. Because of its fundamental roles, much effort has been devoted to the fast and high accuracy solution of nonlinear optimization problem, and subsequently a great deal of models have been proposed and investigated for solving it [8].…”
Section: Introductionmentioning
confidence: 99%